2022
DOI: 10.3389/fphar.2021.788155
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Alliance and Rapport Modulate Responses to Psilocybin Assisted Therapy for Depression

Abstract: Background: Across psychotherapeutic frameworks, the strength of the therapeutic alliance has been found to correlate with treatment outcomes; however, its role has never been formally assessed in a trial of psychedelic-assisted therapy. We aimed to investigate the relationships between therapeutic alliance and rapport, the quality of the acute psychedelic experience and treatment outcomes.Methods: This 2-arm double-blind randomized controlled trial compared escitalopram with psychedelic-assisted therapy for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 110 publications
(188 reference statements)
3
62
1
2
Order By: Relevance
“…In support of this notion, a recent survey study found that individuals who attended group psychedelic ceremonies and felt they had a positive relationship with the ceremony facilitators self-reported greater improvements in wellbeing than those who did not ( Kettner et al, 2021 ). Additionally, Murphy et al (2022) recently found that the strength of the therapeutic relationship in the preparation phase of a course of psilocybin-assisted treatment for depression predicted greater emotional-breakthrough and mystical-type experience in the medicine session, which in turn led to greater reductions in depressive symptoms. The lack of attention paid by most current PAP models to relational aspects of treatment may represent another under-characterized avenue of therapeutic benefit in PAP and a missed opportunity for therapist training.…”
Section: Assessment Of Prior Psychedelic-assisted Psychotherapy Modelsmentioning
confidence: 99%
“…In support of this notion, a recent survey study found that individuals who attended group psychedelic ceremonies and felt they had a positive relationship with the ceremony facilitators self-reported greater improvements in wellbeing than those who did not ( Kettner et al, 2021 ). Additionally, Murphy et al (2022) recently found that the strength of the therapeutic relationship in the preparation phase of a course of psilocybin-assisted treatment for depression predicted greater emotional-breakthrough and mystical-type experience in the medicine session, which in turn led to greater reductions in depressive symptoms. The lack of attention paid by most current PAP models to relational aspects of treatment may represent another under-characterized avenue of therapeutic benefit in PAP and a missed opportunity for therapist training.…”
Section: Assessment Of Prior Psychedelic-assisted Psychotherapy Modelsmentioning
confidence: 99%
“…One can draw parallels between critical slowing in CST and sensitivity to perturbation. In psychedelic therapy, greater sensitivity to perturbation could be related to the strongly hypothesised exaggerated influence of context on outcomes , some concrete examples of which include sensitivity to the therapeutic alliance (Murphy et al 2022), suggestibility (Carhart-Harris et al, 2015 and the music played during the dosing session (Kaelen et al, 2018). If the contextual conditions are adverse, however, one can imagine how small perturbations could cause spiralling ruminative 'loops' that are difficult to break out of.…”
Section: Destabilisation and Psychedelic Therapymentioning
confidence: 99%
“…While specific manipulations of the context (e.g., administering a psychedelic in an adverse or unsupportive environment) may be ethically problematic, measurement of individual's perception of the context (e.g., their relationship with their guides/therapists; Murphy et al, 2022), grading the extent of environmental support (e.g., from low to very high), and naturalistic research, may aid in understanding the effects of context on belief relaxation and revision (Carhart-Harris et al, 2018c).…”
Section: From Belief Relaxation To Belief Revisionmentioning
confidence: 99%